PENGARUH PEMBERIAN REWARD TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA KELASbVII MTS HIDAYATUS SHIBYAN CENDORO PALANG TUBAN - Humaeroh, Ika Fera; Anshori, Sholihul (PAI FAI UNHASY Tebuireng Jombang, 2022)
This study describes the effect of givingirewards on increasing studentimotivation in class VII MTs Hidayatus Shibyan Cendoro. Giving rewards is a form of appreciation given to students for their achievements. Giving rewards is one way to make students more enthusiastic in learning and can motivate students. This study uses quantitative research methods with reward as variable X and learning motivation as variable Y. The population is 110 with a sample of 50% of the population, namely 55 samples. The resultsi of this studyi state that the rewardihas been given with evidence of respondents who answered SS as much as 25%, answered S as much as 18.2%, who answered RR as much as 7.9%, TS as much as 6.4% and who answered STS as much as 2.25 %. And student learning motivation is evidenced by respondents who answered SS as much as 26.4%, answered S as much as 26.2%, who answered RR as much as 5.6%, TS as much as 2.16% and who answered STS as much as 3%. Sooit can be concludedothat there is a relationshipibetween reward and learning motivationiwith a significant correlation of 0.837.